Nitrogen addition alters elemental stoichiometry within soil aggregates in a temperate steppe - J. Yin; R. Wang; H. Liu; X. Feng; Z. Xu; Y. Jiang (Solid Earth, 2016)
Ongoing increases in anthropogenic nitrogen (N) inputs have largely affected soil carbon (C) and nutrient cycling in most terrestrial ecosystems. Numerous studies have concerned the effects of elevated N inputs on soil dissolved organic carbon (DOC), dissolved inorganic N (DIN), available phosphorus (AP), exchangeable calcium (Ca) and magnesium (Mg), and available iron (Fe) and manganese (Mn). However, few have emphasized the stoichiometric traits of these soil parameters, especially within different soil aggregate fractions. In a semiarid grassland of Inner Mongolia, we studied the effect of N addition on the ratios of DOC : DIN, DOC : AP, DIN : AP, exchangeable Ca : Mg, available Fe : Mn within three soil aggregate classes of large macroaggregates (> 2000 µm), small macroaggregates (250–2000 µm), and microaggregates (< 250 µm). Elevated N inputs significantly decreased the DOC : DIN ratio within three soil aggregates. The soil DOC : AP ratio significantly decreased along with increasing N gradients within large macroaggregates and microaggregates. Nitrogen significantly decreased the ratio of exchangeable Ca : Mg within soil macroaggregates. The ratio of available Fe : Mn decreased with N addition within three soil aggregate classes. Alteration of elemental stoichiometry within soil fractions that are characterized by different nutrient retention capacity will influence the chemical composition of soil microorganisms and plant quality.